Effect of polypropylene and steel fibers on web-shear resistance of deep concrete hollow-core slabs - Nguyen, Hang T. N. (2021)
Twelve shear tests were conducted on fiber-reinforced precast/prestressed concrete hollow-core (PCHC) slabs to quantify the effectiveness of polypropylene (pp) and steel fibers (hooked and high-strength/straight types) on shear resistance. Different volume fractions of pp fibers (0.11 and 0.22%) and steel fibers (0.51 and 0.89%) were investigated. The experimental results showed that there were moderate increases in shear strength with the use of pp fibers while substantial increases in shear resistance were observed with the use of steel fibers. In addition, shear strength increased with steel-fiber content. Moreover, with the same steel fiber content of 0.89%, specimens with high-strength/straight fibers exhibited superior performance in shear resistance compared to specimens using hooked steel fibers. In addition, web-shear failure occurred in the majority of specimens. However, as steel fiber content was increased up to 0.89%, in some instances, failure mode shifted from web-shear to flexural-shear failure. In addition, the 2010 fib model code formula for shear strength of steel-fiber-reinforced-concrete (SFRC) members was used to estimate shear capacity of the tested slabs using steel fibers. The calculations showed that the fib model code was overly conservative for shear-strength predictions of SFRC hollow-core slabs reported in this investigation. A semi-empirical formula to calculate shear strength of hollow-core slabs with steel fibers was proposed. It was verified using a database including the 6 shear-test results from this study and another 39 shear-tests on SFRC hollow-core slabs compiled from literature. The formula had a mean value of 1.12 for the ratio of experimental shear strength to calculated shear strength with a coefficient of variation of 0.21.